Nonclassical Symmetry Analysis of Boundary Layer Equations. (1st November 2012) - Naz, Rehana; Khan, Mohammad Danish; Naeem, Imran
Abstract : The nonclassical symmetries of boundary layer equations for two-dimensional and radial flows are considered. A number of exact solutions for problems under consideration were found in the literature, and here we find new similarity solution by implementing the SADE package for finding nonclassical symmetries.